Empathic Psychology: A Code of Risk Prevention and Control for Behavior Guidance in the Multicultural Context - Yi, Kui; Li, Yi; Peng, Huaxin; Wang, Xingrong; Tu, Rungting (Frontiers in Psychology, 2021)
This study aims to uncover the relationship among multicultural differences, empathy and the behaviors of risk prevention and control in the context of crisis events by using a sample of 300 individuals in 10 different multi-culture countries. A theoretical logic model was applied to empirical analysis, and the results indicated that cultural differences positively influenced the behavior of empathy communication and risk prevention and control. Further analyses revealed that real-time monitoring of changes in empathy could provide better options of measures for local risk prevention and control when the same crisis event occurred in multi-culture context. This paper expects to contribute to circumvent cognitive errors caused by cultural differences, and to further provide effective conduction for individuals' risk prevention and control behaviors.